Characteristics of injuries resulting from falls from height in the construction industry - Venkataraman Anantharaman; Thajudeen Mohammed Zuhary; Hao Ying; Natarajan Krishnamurthy (Singapore Medical Journal)
Introduction: Falls from heights contribute to 34% of fatal accidents in Singapore. Of these, 51% of the accidents occur in the construction industry. This retrospective review, of all persons falling from heights in the construction industry from 2006 to 2012 and attending a major hospital, analysed injury patterns and related them to mechanisms and contributory factors. Methods: Information collected included injury and casualty characteristics, safety measures, pre-existing medical conditions and clinical outcomes. Results: Of 1,085 patients, 951 were male with a mean age of 39.8 years, mean height of 165.9 cm and mean weight of 69.7 kg. Most of the casualties fell between 0800 and 2000 hours. Among the severely injured patients, 2.4% had head injuries, 54.9% had chest injuries and 39.2% had abdominal and pelvic injuries. For these casualties, the mortality rate was 60.8%. For patients with less than major trauma, the commonest injuries were in the lower limbs (41.8%), upper limbs (40.8%) and spine (22.2%). All the casualties survived. Falls from scaffolding, formwork and platforms were the most common causes of severe injuries (41.1%). Safety helmets and harnesses were reported to be used in 1.8% and 4.1% of instances of falls, respectively. Conclusion: Studying the patterns of injuries following falls at construction sites has the potential for injury prevention through safe practices, use of safety equipment and targeted training.